2017
DOI: 10.1038/srep45400
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Imaging Evaluation of Renal Cell Carcinoma Subtypes with Grating-based X-ray Phase-contrast CT

Abstract: Current clinical imaging methods face limitations in the detection and correct characterization of different subtypes of renal cell carcinoma (RCC), while these are important for therapy and prognosis. The present study evaluates the potential of grating-based X-ray phase-contrast computed tomography (gbPC-CT) for visualization and characterization of human RCC subtypes. The imaging results for 23 ex vivo formalin-fixed human kidney specimens obtained with phase-contrast CT were compared to the results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…The similar radio-opaque properties of lead and tungsten are however, a possible drawback of such an experimental set up. An alternative innovative CT based approach using phase contrast has been reported, which enabled the ex vivo depiction of human renal carcinoma specimens without contrast agents, making use of the x-ray phase shift that occurs due to different passing characteristics of matter 25 . We showed that the process of PTA staining preserved the tissue without any shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…The similar radio-opaque properties of lead and tungsten are however, a possible drawback of such an experimental set up. An alternative innovative CT based approach using phase contrast has been reported, which enabled the ex vivo depiction of human renal carcinoma specimens without contrast agents, making use of the x-ray phase shift that occurs due to different passing characteristics of matter 25 . We showed that the process of PTA staining preserved the tissue without any shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our study, the clear-cell RCC patients would potentially receive more therapeutic benefit of PN than RN. Fortunately, with the advance development of imaging technology, current clinical imaging methods are developed in the detection and correct characterization of different RCC subtypes, such as using the Grating-based X-ray Phase-contrast CT[ 21 ], multiphasic multidetector computed tomography (MDCT) scan[ 22 ] and 18F-fluorodeoxyglucose-PETCT[ 23 ].This clinical imaging information may contribute to treatment plan by the urologist.…”
Section: Discussionmentioning
confidence: 99%
“…It has been evidenced that multiphasic CT is useful for distinguishing the benign vs. malignant renal masses and discriminating the pathological subtypes of RCC ( 20 , 21 ). In the study, chRCC tends to be homogenous, solid, well circumcised and without calcification.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, chRCC tends to be homogenous, solid, well circumcised and without calcification. Braunagel M, et al ( 21 ) compared the CT imaging which features different subtypes of renal cell carcinoma (RCC), it was concluded that chRCCs were the most homogeneous tumors with fibrous strands and microbleeding without detection of hyalinization or necrosis. According to Zhang J's study ( 22 ), heterogeneous renal lesions were more likely to behaving aggressively.…”
Section: Discussionmentioning
confidence: 99%